Peran work engagement sebagai variabel intervening pada pengaruh psychological well being dan work environment terhadap employee performance pada PT Pelabuhan Indonesia (Persero) Regional 3 Kantor Surabaya - Resa Salsa Pashiera; Budiono Budiono (Jurnal Ilmu Manajemen, 2023)
This study aims to study the effect of psychological well-being and work environment on employee performance through work engagement in PT Pelabuhan Indonesia Regional 3 Surabaya Office. This study uses a type of causality research that uses quantitative. This study employs a quantitative method of causality research. Stratified random sampling is a method of sampling. Fifty-four employees have responded. With SmartPLS 4.0 program, the Structural Equation Model (SEM) was used for the statistical analysis in this study. The results showed that psychological well-being and work engagement has a positive and significant effect. The work environment has a positive and significant effect on work engagement. Work engagement positively and significantly impacts employee performance. Employee performance was not positively impacted by psychological well-being. The work environment has a positive and significant effect on employee performance. Work engagement mediates the effect of psychological well-being on employee performance. Work engagement does not mediate the effect of the work environment on employee performance